Impact of neighbourhood facilities towards locational decision and residential property value - Mohd Dlan, Najihah (2016)
Each type of property has its own attributes that imposed significant impact to the property value and buying decisions. From the past studies the attribute which could gave impact to the location decisions and property valuea were social, physical, economic and environment. In this study, researcher examined the impact of the neighbourhood facilities towards the locational decisions of the potential buyers and residential property value in case study area. The research objectives of this study were to identify the existing pattern and layout of neighbourhood facilities attributes in case study area as well as to ascertain the classification of neighbourhood facilities attributes follow the current existing pattern and layout in case study area. Besides, this study aimed investigated the significant of the identified neighbourhood facilities attributes influencing value of the residential properties in case study area and investigate the significant of the identified neighbourhood facilities attributes influencing the locational decisions in case study area. The researcher adopted mixed method approach and data collection method was mainly based on the relevant documents such as Kajang Municipal Council and Sepang Municipal Council Local Plans as well as the document review from NAPIC, interview and observation in the case study area. The method analysis was done by using Thematic Analysis, Mann Whitney U Test Analysis and Trend Analysis. The findings indicate the area of study was divided into 16 sections and the neighbourhood facilities‟ attributes were further categorized as “institutional and community facilities”, “open space and recreationconveniences” and “accessibility.” The general finding of this study reveal that there are significant relationship between some of neighbourhood facilities such as shopping complexes, schools, sport accomodation, highway accessibility and worship centers towards location decisions as well as values of the residential properties in Bandar Baru Bangi.